Understanding the experiences of lung volume recruitment among boys with Duchenne muscular dystrophy: A multicenter qualitative study. Issue 1 (23rd September 2022) - Katz, Sherri L.; Blinder, Henrietta; Newhook, Dennis; BMUS, Leana Azerrad; Nicholls, Stuart; McMillan, Hugh J.; Mah, Jean K.; Campbell, Craig; McAdam, Laura C.; Zielinski, David; Toupin‐April, Karine; Momoli, Franco; et al.
Abstract: Background: Despite recommendations for regular lung volume recruitment (LVR) use in clinical practice guidelines for children with neuromuscular disease, adherence to LVR is poor. We aimed to describe the experience of LVR by boys with Duchenne muscular dystrophy (DMD), their families, and healthcare providers (HCPs), as well as to identify the barriers and facilitators to LVR use. Methods: This multicenter, qualitative study evaluated boys with DMD ( n = 11) who used twice‐daily LVR as part of a randomized controlled trial, as well as their parents ( n = 11), and HCPs involved in the clinical use of LVR ( n = 9). Semistructured interviews were conducted to identify participants' understanding of LVR therapy and their beliefs, barriers and facilitators to its use. Thematic analysis was conducted using an inductive approach. A subanalysis compared adherent and nonadherent children. Results: Seven themes were identified related to participants' beliefs and experiences with LVR: emotional impact, adaptation to LVR, perceived benefits of LVR, routine, family engagement, clinical resources, and equipment‐related factors. Strategies to improve adherence were also identified, including education, reinforcement and demonstration of LVR benefit, as well as clinician support. There were no thematic differences between adherent and nonadherent children. Discussion: Despite the benefits of LVR and positive experiences with it by many families, there remain barriers to adherence to treatment. HCPs need to balance the need for early introduction to give families time to adapt to LVR while ensuring that the benefit of LVR outweighs the burden. Clinician support is important for family engagement.